Cascade of Remainders. Issue 2 (November 2016) - DeArmitt, Pleshette
Abstract : In a very late essay on remains, one might say a throw away essay, Derrida doggedly tracks the relation of a certain desire to remains, linking it to sacrificial economy and to a hierarchical ontological order. If our concern is a thinking of desire as it pertains to remains, why should we not turn first, or perhaps exclusively, to Derrida's monumental works on the subject of remains, specifically Glas and Cinders, jettisoning the little-known essay we have not yet named? Certainly Derrida has said much in these well-known works about desire and remains, consumption and excretion, fire and ashes. So, why devote all one's attention, as we will do in this paper, to what might be said to be a morsel of an essay, which has remained largely unread and hence falls outside of Derrida commentary? The essay in question is his 2002 'Remains – the Master, or the Supplement of Infinity', a homage to Charles Malamoud, a French ethnologist and scholar of Indian and Oriental religions whose work, especially his 1989 Cooking the World, was influential on Derrida's thinking concerning the 'rhetorics of cannibalism' and 'eating the other' and featured prominently in his seminars from 1989–1991 on the aforementioned themes. In 'Remains – the Master', a dense and rich essay, Derrida analogically links two vastly different cultures – the Brahmanic of India and the Greco-European – in terms of a 'law of remainders', which for both traditions, he claims, is an organizing principle of humans, gods, and the whole of the world. In his essay Derrida returns to or, more accurately, remains with a thinking of 'the French word " reste ", the remnants [ restance ] of " reste "', which, as Derrida notes, is 'difficult to translate in an exhaustive or transparent manner, ' that is, 'without remainder' (2002, 41). However, what this paper will follow is the circulation of remainders in the Vedic tradition, as analysed by Derrida and Malamoud. In doing so, we can begin to not only translate the notion of Malamoud's 'cascade de restes' from one culture, logic, and idiom to another but understand how for Derrida this ritual downpour of remainders not only institutes a hierarchy of remainders but also produces ipseity.